Assessing the Computation and Communication Overhead of Linux Containers for HPC Applications - Alles, Guilherme Rezende; Carissimi, Alexandre; Schnorr, Lucas Mello (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2018)
Virtualization technology provides features that are desirable for highperformance computing (HPC), such as enhanced reproducibility for scientific experiments and ﬂexible execution environment customization. This paper explores the performance implications of applying Operating System (OS) containers in HPC applications. Docker and Singularity are compared to a native baseline with no virtualization, using synthetic workloads and an earthquake simulator called Ondes3D as benchmarks. Our evaluation using up to 256 cores indicate that (a) Singularity containers have minor performance overhead, (b) Docker containers do suffer from increased network latency, and (c) performance gains are attainable with an optimized container on top of a regular OS.